It’s too dark in here: Bornman, E, van Eeden, R & Wentzel M (eds) (1998) Violence in South African: A variety of perspectives. Pretoria: Human Sciences Research Council . ISBN 0-07969-1858-9. 457 pages - Ratele, Kopano (PINS-Psychology in Society, 2026)
We are not out of the woods yet. With a bit of good luck, and a lot of work, we might be a few years before we reach the (high) road. Here is some work; as for luck - well, we’ll keep working. And, true, we had good warning. Decolonisation, they said, is an historical phenomenon. Decolonisation, they told us, spells violence (Fanon, 1967) - for what we are experiencing in varying guises is an uneven process of decolonisation. Bornman, van Eeden and Wentzel’s collection of articles is then one other effort to unravel the historical, social, biological, political and relational aspects of the phenomenon of violence, and, whether consciously or unawares, to look into the processes which have been called national liberation, post-apartheid, African renaissance, or reconciliation, but which always are historical and thus about colonisation. Thus, in bringing together a group of young and experienced scholars and researchers from a variety of disciplines, institutional locations, and theoretical positions to bear on what has gone before In South African between the 1960s and 1997, and the book is attempt to venture not only on how we got here but also on the future of that history.